Meteorites as a scientific heritage - Franza, Annarita (2021)
This paper investigates the importance of meteorites as a scientific heritage. While the significance of meteorites as natural heritage is relatively easy to establish, the implication of their meaning as scientific heritage may be more difficult to define. With this aim in mind, in this paper, we present the catalogue standards for meteorite specimens, preserved either in natural history museums or in private collections, proposed by the Italian Istituto Centrale per il Catalogo e la Documentazione – ICCD (Central Institute for Catalogue and Documentation). This work outlines the structure of the catalogue card that describes the meteorite specimen along with other information related to the sample (e.g., archival documentation on collectors and traders, museum catalogues and inventories, general bibliography). This paper concludes discussing the cataloguing, according to ICCD standards, of two Renazzo meteorite specimens, which fell in the eponymous Italian village in 1824 and are now preserved at the Natural History Museum of the University of Firenze.   Received: 2020-4-21 Revised: 2020-8-8 Accepted: 2020-8-13 Online: 2020-11-4 Publication: 2021-2-10